Mechanical Characteristics of Plastic Films Made from Potato Peel Waste (solanum tuberosum L.) with Variations of Acetic Acid and CMC - Rahmawati, Fira; Hakim, Muhammad Fahmi; Ni’mah, Kamilah Pathun (Jurusan Ilmu dan Teknologi Pangan, Fakultas Pertanian,, 2023)
West Java produces 1,3 thousand million tons of plastic waste per year. Synthetic plastics have component materials that are not environmentally friendly and can decompose for 20 years, therefor handling is required to overcome the accumulation of plastic waste. 3R (reduce, reuse, recycle) is applicable way example using plastic materials that are easily decomposed. Starch in potato skins can be used as a material for bioplastics components, the purpose of this research is to make plastic films made from potato peel waste (Solanum tuberosum L.), as an alternative natural polymer to alternate petroleum materials. Various concentrations of acetic acid (1% and 2%) and variations of carboxymethyl cellulose (1,5 gr and 2,1 gr) were added to the samples and two repetitions, the result of all is 10 samples. Firstly the potato skins were extracted to extract the starch, then the starch was dried at 40 oC for 8 hours. The procedure for making plastic film is to mix the raw materials and gelatinization at 70 oC for 120 minutes. The plastic film is shaped, dried and finally, it does a mechanical test. The research shows that variations of acetic acid and CMC can increase the mechanical properties of tensile strength, elongation at break, thickness, and water uptake. The best plastic film composition was produced using 1% acetic acid and 2,1 gr CMC. The sample has a tensile strength value of 15,72 N/mm2, elongation at break of 14,29%, thickness of 146,17 µm, and water absorption of 365%.